A case for the extension of the 'comply or explain' philosophy to a national code of corporate governance in Zimbabwe: a comparative analysis - Simbo, Chiedza (Department of Commercial Law, 2026)
After the wave of corporate collapses in the United Kingdom (UK) in the late 1980s and early 1990s, a need for corporate governance reform was realised in that country. There was an introduction of self-regulation as a method of corporate governance. The private sector initiated efforts to improve corporate governance leading to recommendations by the Cadbury, the Greenbury, the Hampel, the Turnbul, the Smith and the Higgs Committees.